2015
DOI: 10.1039/c4cc07411d
|View full text |Cite
|
Sign up to set email alerts
|

A fast-responsive mitochondria-targeted fluorescent probe detecting endogenous hypochlorite in living RAW 264.7 cells and nude mouse

Abstract: A very fast-responsive fluorescent probe PZ-Py for imaging mitochondrial HClO/ClO(-), with a relatively long emission wavelength, was prepared. The limit of detection was evaluated to be 17.9 nM. Moreover, the probe PZ-Py was successfully applied in the imaging of endogenous HClO/ClO(-) in the mitochondria of RAW 264.7 cells and living nude mouse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(71 citation statements)
references
References 32 publications
2
69
0
Order By: Relevance
“…In recent years, fluorescence imaging technique based on chemical probe make the in situ tissue quantification possible 12 , a precondition of which is the need to design a rapid and sensitive probe for the target. Many excellent chemical probes have been devised to monitor the ROS molecules like ClO -in various biological samples [13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, fluorescence imaging technique based on chemical probe make the in situ tissue quantification possible 12 , a precondition of which is the need to design a rapid and sensitive probe for the target. Many excellent chemical probes have been devised to monitor the ROS molecules like ClO -in various biological samples [13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure S6, upon the addition of HOCl into the aqueous solution of PQI , the molecular ion peak of [ PQI ] + at m / z= 423.1905 was disappeared. A new peak at m / z= 439.1848 was obtained, which can be assigned to the oxidized sulfoxide product, PQI‐O . The result indicated that the HOCl‐induced oxidation of thiazine thioetherto sulfoxide is responsible for the HOCl sensing mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Another sulfide‐based fluorescent probe for the selective detection of HOCl was reported by Wang and co‐workers in 2015 (Scheme ) . The methylated pyridinium group of the chemical probe exhibits not only a new type of effective mitochondria‐targeting group (due to the positive charge within the molecule), but also assists in the water‐solubility of the organic fragment of the molecule.…”
Section: Introductionmentioning
confidence: 99%